Качественные показатели воскоподобных веществ - Омельченко, Юлия Евгеньевна; Демидов, Игорь Николаевич (НТУ "ХПИ", 2016)
В статье представлены результаты исследования качественных показателей воскоподобных веществ извлеченных из вторичных продуктов производства растительного масла методом контактной экстракции с использованием в качестве растворителей гексан и сивушное масло. Проанализирован качественный состав исследуемых образцов методом газовой хроматографии. Исследованы основные качественные показатели воскоподобных веществ и проведена сравнительная характеристика с промышленными аналогами.

The article presents the results of qualitative research wax-like substances extracted from recycled vegetable oil production by extraction of the contact using hexane as a solvent and fusel oil. The aim of this work is to determine the physical and chemical indicators obtained wax-like substances. To address this goal the study used the method of gas chromatography, differential scanning calorimetry and the traditional chemical analysis methods. We analyzed by gas hramatografii qualitative composition of the test samples, allowing dentify more than 90% of wax esters. Installed temperature melting wax-like substances of the samples by methods of open capillary and differential scanning calorimetry, which amounted to 81ºS and 73,5ºS for hexane and fusel oil, respectively. The basic physical and chemical characteristics of wax-like substances, namely, acid number, saponification number, the essential number and iodine number. The comparative characteristic of physical-chemical indicators of the samples wax-like substance with industry peers. Comparative characteristics showed that the content of related substances in the test samples did not exceed the permissible values in comparison with beeswax and wax derived from the husks of sunflower seeds
Quality indicators waxlike substances
Keywords: масложировая отрасль; рафинация; хроматография; дифференциальная сканирующая калориметрия; температура плавления; контактная экстракция; waxy substances; chromatography; differential scanning calorimetry; melting temperature